Correlations between the active straight leg raise, sleep and somatosensory sensitivity during pregnancy with post-partum lumbopelvic pain: An initial exploration - Beales, Darren; Gaynor, O.; Harris, J.; Fary, Robyn; O'Sullivan, Peter; Slater, Helen; Graven-Nielsen, T.; Palsson, T. (Walter de Gruyter GmbH, 2018)
© 2018 Scandinavian Association for the Study of Pain. Published by Walter de Gruyter GmbH, Berlin/Boston. All rights reserved. For some women, lumbopelvic pain (LPP) developed during pregnancy becomes a continuing post-partum problem. Increased understanding of potential prognostic factors is required. This study investigated whether active straight leg raise (ASLR), sleep dysfunction and pressure pain sensitivity during pregnancy are correlated with LPP intensity and quality, disability, and physical health-related quality of life (HRQoL) post-partum. An exploratory, prospective cohort study design was used. Baseline factors of interest were: (1) ASLR, (2) Pittsburgh Sleep Quality Index, and (3) pressure pain thresholds (PPTs) collected from pregnant women from sites local and distal to the lumbopelvic area. Follow-up data collected 11-18 months post-partum (n=29) were: (1) pain intensity score (numerical rating scale), (2) pain quality (McGill Pain Questionnaire), (3) disability (Pelvic Girdle Questionnaire), and (4) HRQoL (36-item Short Form Health Survey). Correlation analysis was performed. Greater difficulty with an ASLR during pregnancy correlated with lower post-partum physical HRQoL scores (r=-0.563, p=0.002). Likewise, reduced PPTs at the sacrum during pregnancy was correlated with a higher post-partum pain quality score (r=-0.384, p=0.040). In this cohort, findings indicate that poor ASLR performance and localised pressure pain hypersensitivity at the pelvis during pregnancy are correlated with post-partum physical HRQoL and pain quality, respectively. Pain sensitivity may contribute to the prognosis of women with LPP during pregnancy. These explorative findings may be important for designing larger prognostic studies and may assist in directing potential pain management in post-partum LPP.